2018
DOI: 10.1016/j.jmoldx.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A Head-to-Head Analytical Comparison of Cobas 4800 HPV, PapilloCheck HPV Screening, and LMNX Genotyping Kit HPV GP for Detection of Human Papillomavirus DNA in Cervical and Cervicovaginal Swabs

Abstract: High-risk human papillomavirus (hrHPV) infection is a cause of cervical cancer development. The addition of hrHPV testing to cervical cancer screening and monitoring of cervical intraepithelial neoplasia treatment improves the efficacy of screening and treatment, respectively. Self-sampling for hrHPV testing seems a promising tool for increasing patient participation in cervical cancer screening. In this project, 1198 cervical swabs obtained by physicians and 176 cervicovaginal swabs obtained by self-sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Cervical swabs and semen samples were tested for HPV DNA using the cobas ® 4800 HPV Test (Roche Diagnostics GmBH, Mannheim, Germany) according to the manufacturer’s recommendations for cervical sample management [ 17 ]. After analysis, DNA extracted using cobas × 480 was used for HPV DNA detection and genotyping using the PapilloCheck ® HPV-Screening kit (Greiner Bio-One, Frickenhausen, Germany) [ 18 ] as described previously [ 19 ]. DNA from penile swabs was isolated using the QIAamp ® DNA detection by Micro kit (Qiagen, Hilden, Germany) and then tested for HPV PapilloCheck ® HPV-Screening kit [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cervical swabs and semen samples were tested for HPV DNA using the cobas ® 4800 HPV Test (Roche Diagnostics GmBH, Mannheim, Germany) according to the manufacturer’s recommendations for cervical sample management [ 17 ]. After analysis, DNA extracted using cobas × 480 was used for HPV DNA detection and genotyping using the PapilloCheck ® HPV-Screening kit (Greiner Bio-One, Frickenhausen, Germany) [ 18 ] as described previously [ 19 ]. DNA from penile swabs was isolated using the QIAamp ® DNA detection by Micro kit (Qiagen, Hilden, Germany) and then tested for HPV PapilloCheck ® HPV-Screening kit [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity slightly improved when analysis was restricted to 14 HR types (72%) or HPV16/18 only (81%). While the NS platform was able to detect a number of HPV types in epidemiological samples with No-PCR, its sensitivity was not comparable to other methods that incorporate target or signal amplification [9,26]. This suggested that sensitivity of the NS platform could be improved with the addition of PCR.…”
Section: Discussionmentioning
confidence: 92%
“…Supported by the Z-test results, we conclude that performance of HPV CodeSets is highly specific and reproducible regardless of the differences in PCR cycle number and diversity of samples (different anatomical sites, varying collection media and fixatives, varying extraction methods). In addition, PCR-15 is the preferred protocol for further validation studies since the products from PCR-15 could be hybridized directly, eliminating errors during dilution, and fewer amplification cycles have the advantage of reducing amplification bias in type detection [26]. The mean numbers of HPV types detected per sample by PCR-15 (5.3), LA (5.8) and TypeSeq (6.3) were similar, further supporting the comparability of the PCR-15 assay.…”
Section: Discussionmentioning
confidence: 99%
“…After analysis, DNA extracted using a cobas x 480 instrument was subjected to HPV DNA detection and genotyping using PapilloCheck® HPV-Screening (Greiner Bio-One, Frickenhausen, Germany) [13]. In 40 samples where cobas® 4800 HPV Test and PapilloCheck® HPV-Screening were not concordant, LMNX Genotyping Kit HPV GP (Diassay, Rijswijk, The Netherlands) [14] was used for confirmation as described previously [12].…”
Section: Methodsmentioning
confidence: 99%